2019
DOI: 10.3390/en12101929
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Assessment of Nano-Particulate Graphene-Water/Ethylene Glycol (WEG 60:40) Nano-Suspension in a Compact Heat Exchanger

Abstract: In the present study, we report the results of the experiments conducted on the convective heat transfer of graphene nano-platelets dispersed in water-ethylene glycol. The graphene nano-suspension was employed as a coolant inside a micro-channel and heat-transfer coefficient (HTC) and pressure drop (PD) values of the system were reported at different operating conditions. The results demonstrated that the use of graphene nano-platelets can potentially augment the thermal conductivity of the working fluid by 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…From the thermal standpoint, the addition of nanoparticles (mainly metal oxides) to a dielectric base oil seems to enhance its thermal conductivity (k) or cooling capacity. This was first noticed with other cooling base fluids, including water and etilenglicol [10][11][12][13]. Regarding their expected behavior as insulators, the presence of nanoparticles in a suspension improves the dielectric strength of the base fluid, as the breakdown voltages (BDV) of the tested nanofluids are usually higher.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…From the thermal standpoint, the addition of nanoparticles (mainly metal oxides) to a dielectric base oil seems to enhance its thermal conductivity (k) or cooling capacity. This was first noticed with other cooling base fluids, including water and etilenglicol [10][11][12][13]. Regarding their expected behavior as insulators, the presence of nanoparticles in a suspension improves the dielectric strength of the base fluid, as the breakdown voltages (BDV) of the tested nanofluids are usually higher.…”
Section: Introductionmentioning
confidence: 87%
“…As in other scientific fields, a possible improvement of the dielectric oils could arise from nanotechnology. The use of nanoparticles is growing in importance in medicine, in detection and treatments against cancer and in the administration of medicines [1,2]; in material science, for obtaining polymers and materials with enhanced properties for several applications [3][4][5]; in the treatment of industrial wastes, as they are able to capture polluting substances [6]; and in energy and thermal engineering, for energy and heat storage and cooling [7][8][9][10]. The research on dielectric nanofluids is being carried out under this context, aiming at the improvement of the cooling and the electrical isolation of the transformer wires.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial increase in the experimental thermal efficiency has then resulted from the combination of the above two conditions. [48][49][50] Table 3 and Figure 10(a) and (b) below illustrate the F R (ta) and F R U L for PEG-TGr-DW nanofluids. When the nanofluid flows at a constant flow rate (0.00833 kg s À1 ) and varied Gr weight concentrations (0.025 wt%, 0.05 wt%, 0.075 wt%, and 0.1 wt%), F R (ta) values progressively increased by 6.28%, 8.49%, 9.68%, and 10.53%, respectively, relative to the data of base fluid.…”
Section: Analysis Of Thermal Efficiency Using H 2 Omentioning
confidence: 99%
“…They found that when compared to zero-field condition, the particles rotate faster and the viscosity of ferrofluid is reduced, leading to enhanced heat transfer rate under an oscillating magnetic field [8]. Many other studies have been carried out investigating the role of nanofluids in the heat transfer rate [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%